Estratégias intergeracionais mobilizadas por famílias no dever de casa de matemática: um estudo sobre práticas de letramento - Antunes, Brenda Cristina (Universidade Federal de São Carlos, 2024)
This dissertation describes the directions and final results of a master's degree investigation, linked to the Postgraduate Program in Education (PPGE) at the Federal University of São Carlos (UFSCar), along with the research line "Education in Sciences and Mathematics" - Axis Mathematics Education. The general objective was to understand what family teaching strategies reveal when solving Mathematics homework, based on the intergenerational issue from the perspective of literacy. As a theoretical framework, we rely on studies of literacy, literacy, numeracy/mathematical literacy, family-school relationships and intergenerational relationships. The methodological approach is part of studies on the family-school relationship, with a qualitative study, whose data produced focused on participant observation of the homework assistance process, in situ by the researcher, as well as from a questionnaire of characterization of family groups that included specific questions about the importance of Mathematics in life. The research theme stands out as fundamental and innovative in the field of Mathematics Education as it presents the possibility of understanding the intergenerational culture of families at a public school in the region of São Carlos-SP. The data produced and analyzed indicate that family members (grandmother and mother), with whom we were in direct contact, use diverse action schemes, ranging from counting on their fingers, support from semi-structured and structured resources, even though they do not have mastery of basic instruments for the adoption of the latter. Thus, studying the family-school relationship, in the context of this work, indicated that this is a rich and promising field to be explored with emphasis on the intergenerational issue that highlighted the need to understand processes of mathematical literacy practices mobilized in homework.
Intergenerational strategies mobilized by families in mathematics homework: a study on literacy practices
Keywords: Relação família-escola; Educação Intergeracional; Dever de casa; CIENCIAS HUMANAS::EDUCACAO